Nilai-Nilai Kearifan Lokal dalam Pengembangan Ilmu Pengetahuan di Pendidikan Tinggi Hukum - Aryanto, Bayu; Wibawa, Iskandar; Achmad H, Dwiyana; Surya, Faizal Adi; Tartila T, Marsatana (Kertha Patrika; Vol 46 No 3 (2024), 2024)
Universities are one of the mouthpieces to achieve the state's goal, which is to educate the nation's life. The need for human resources is not enough if you only rely on knowledge, but other skills are also needed, including practical skills. In line with this, it is important to see the development of science in higher education based on local wisdom values. The purpose of this research is to see the relationship between local wisdom values in the development of science in law higher education. The research method used is normative juridical. The result of the research is that the optimization of Local Wisdom in good education will create superior human resources and advance a country. The higher the quality of education in a country, the more advanced the country is. On the other hand, the lower the quality of education in a country, the more backward the country will be. Seeing this, it is interesting to examine the value of local wisdom as a development of science. There is a connection between local wisdom values, one of which is gusjigang which can be the foundation in legal science in law colleges.